2014
DOI: 10.1186/s40163-014-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality in criminological research

Abstract: Since the pioneering early studies of the 1990s hinted at its promise as a research method, virtual reality (VR) technology has increasingly been used by social scientists. Given recent developments that have greatly enhanced realism, reduced costs, and increased possibilities for application, VR seems well on its way to become an established research tool in the social sciences. However, as with other methodological innovations, the field of criminology has been slow to catch on. To address this gap, this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The use of this immersive technique has the benefits of (i) reducing the influence of researcher questioning, as participants are required to freely respond to contextual cues, and (ii) eliciting more genuine and valid responses, as participants are immersed in the environment rather than relying on their imagination (Van Gelder et al, 2016). It also addresses one of the main challenges of criminology, by allowing us to get far closer to observing real world behavior in an ethical manner, whilst also increasing the motivation of participants to share their experiences, skills and motivations for committing crime and/or burglary (Van Gelder, Luciano & Otte, 2014).…”
Section: The Use Of the Virtual Enactment Methods -Benefits Over Lessmentioning
confidence: 99%
“…The use of this immersive technique has the benefits of (i) reducing the influence of researcher questioning, as participants are required to freely respond to contextual cues, and (ii) eliciting more genuine and valid responses, as participants are immersed in the environment rather than relying on their imagination (Van Gelder et al, 2016). It also addresses one of the main challenges of criminology, by allowing us to get far closer to observing real world behavior in an ethical manner, whilst also increasing the motivation of participants to share their experiences, skills and motivations for committing crime and/or burglary (Van Gelder, Luciano & Otte, 2014).…”
Section: The Use Of the Virtual Enactment Methods -Benefits Over Lessmentioning
confidence: 99%
“…For example, studies on treatment effectiveness for people suffering from specific phobias have shown that VR-based exposure treatment can be as effective as traditional forms of exposure therapy (Parsons and Rizzo 2008;Powers and Emmelkamp 2008). Importantly, findings from VR research suggest that virtual environments can be usefully employed as substitutes for real-world settings when practical or ethical considerations militate against using their real-life equivalents, as behavior in virtual environments can closely mimic behavior in comparable real-world settings (Slater et al 2006(Slater et al 2013Van Gelder, Otte, and Luciano 2014).…”
Section: Virtual Reality As a Research Methodsmentioning
confidence: 99%
“…To enhance the ecological validity of laboratory studies, researchers have recently advocated the use of virtual reality technologies (van Gelder, Otte, & Luciano, 2014). For example, in a recent study, Slater et al (2013) simulated an immersive barroom fight and found evidence that social group membership may increase the likelihood of bystander intervention.…”
Section: Experiments: Laboratory and Field Interventionsmentioning
confidence: 99%